EDUKASI PEMANTAUAN TUMBUH KEMBANG ANAK UMUR 3-5 TAHUN - Satria, Epi; Aninora, Novia Rita; Faisal, Afrah Diba (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2022)
Motor development is the process of growth and development of a child's ability to move. Basically, this development develops in line with the maturity of the nerves and muscles of the child. The form of community service activities carried out is the implementation of counseling to mothers about the level of development of children under five to pre-school. carried out at Uswatun Hasanah Kindergarten, Padang in 2021. This community service activity aims to increase mother's knowledge about the growth and development of children at the age of 3-5 years. In an effort to monitor child development so that mothers can provide good and appropriate care for the growth process and child development. The result of this community service is that all mothers in Uswatun Hasanah Kindergarten know about the growth and development of children aged 3-5 years. With good knowledge, mothers can monitor their child's growth and development. Keywords: Knowledge, child development